Mustelids as bioindicators of the environmental contamination by heavy metals. (November 2018) - Goretti, E.; Pallottini, M.; Cenci Goga, B.T.; Selvaggi, R.; Petroselli, C.; Vercillo, F.; Cappelletti, D.
Graphical abstract: Highlights: We elaborated an index to assess metal contamination in terrestrial environments. The index evaluates the heavy metals bioaccumulation in selected tissues of mustelids. Stone and pine marten have a complementary role in contamination assessment. High index values in both species show a pollution in rural and suburban habitats. High index values only for stone marten show a pollution limited to suburban habitats. Abstract: Cadmium (Cd), lead (Pb), zinc (Zn) and copper (Cu) concentrations in the liver and the quadriceps muscle of adult stone marten (9 specimens) and pine marten (11 specimens) from Central Italy were assessed. No significant difference in the heavy metal values for each of the two selected tissues was detected for the two mustelid species. The measured heavy metal values were generally below the contamination level ranges from other areas of Central Italy and Croatia, except for the Cd in this latter area. Toxic Contamination Index (TCI) values for Cd showed high contamination levels both in the stone marten (most synanthropic species, colonizing mainly suburban environments) and in pine marten (species less adaptable to the anthropic environments, colonizing mainly rural and forest environments). High TCI values for Pb were detected only in stone marten. This fact indicates a higher Pb contamination in suburban habitats, probably due to the past use of leaded gasoline and still currently released by several anthropogenic activities, as the industrial emissions of mineral processing and incinerators, making Pb one of the most common heavy metal contaminant in soils. The present study suggests that stone marten and pine marten can be good bioindicators with a complementary role regarding the evaluation of the heavy metal contamination in a given territory. When high levels of TCI (in our case for Cd) are detectable in selected tissues of both stone marten and pine marten, it means that we are in the presence of widespread pollution. On the other hand, when this condition is observed only for stone marten (in our case for Pb), it means that we are in the presence of a local contamination mainly localized in areas with high anthropization.